Performance of anaerobic immersed membrane bioreactor (AnIMBR) treating synthetic dairy wastewater. Issue 47 (7th October 2016) - Al-Malack, Muhammad H.; Aldana, Gerardo R.
Abstract: The performance of a bench-scale anaerobic immersed membrane bioreactor (AnIMBR) when treating synthetic dairy wastewater was investigated. The investigation was carried out at mixed liquor suspended solid (MLSS) concentrations of 5, 000, 1, 0000, and 1, 5000 mg/l and influent chemical oxygen demand (COD) concentrations of 2, 000, 4, 000, 6, 000, and 8, 000 mg/l. In order to avoid frequent membrane fouling, the investigation was conducted at permeate flux of about 2.2 l/m 2 h. Results of the investigation showed that maximum removal efficiencies of COD (91.4 percent) and turbidity (99.4 percent) were achieved at MLSS and influent COD values of 15, 000 and 4, 000 mg/l, and 15, 000 and 2, 000 mg/l, respectively. A maximum biogas yield of 0.17 l/g CODr with methane content of 82 percent was obtained at an MLSS value of 15, 000 mg/l. Mathematical relationships between daily biogas production and MLSS and influent COD concentrations were formulated. Throughout the investigation, sludge production was at an average of 0.022 mg VSS/mg CODr . Results of the investigation also showed that total phosphate could be removed by more than 86 percent, which was achieved at an MLSS value of 5, 000 mg/l.